Pelatihan Peningkatan Tataniaga Daun Ketepeng Sebagai Bahan Dasar Pembuatan Hand Sanitizer Pada Masyarakat Desa Huluduotamo Kecamatan Suwawa Kabupaten Bone Bolango - Bakari, Yuliana; Wibowo, Larasati Sukmadewi (Universitas Negeri Gorontalo, 2022)
This community service activity aims to provide direct education and training to the community regarding the trade system in the use of ketepeng leaves to be processed into Hand Sanitizer which can provide business opportunities to several communities affected by COVID-19. As a medicinal plant, ketepeng leaves have other benefits therea are choosing anti-bacterial content and can be processed into other products. The location of the activity is in the village of Huluduotamo, Suwawa District. This hand sanitizer from the ketepeng plant can be used as an alternative to waterless hand sanitizer that is easy to make and applied to the community. Based on the evaluation results through discussions with teenagers that the community has a high enthusiasm for implementing the manufacture of hand sanitizers because the manufacturing process is relatively easy and the availability of raw materials is abundant in the village.